Profitability and Liquidity Moderated The Effect of Managerial Ownership, Institutional Ownership, Free Cash Flow, Growth and Size on Debt Policy - Pribadi, Bagus; Haryono, Nadia Asandimitra; Hartono, Ulil (Profesional Muda Cendekia Publishing, 2024)
Research Aims: This study aims to determine the effect of managerial ownership, institutional ownership, free cash flow, growth, size with profitability and liquidity as moderating variable in manufacturing sector companies listed on the Indonesia Stock Exchange for the period 2018-2022. Design/methodology/approach: Research was proceed using quantitative methods with secondary data. The sampling method used purposive sampling involving 58 research samples. This research analysis technique employed moderated regression analysis. Research Findings: The results of this study indicated that managerial ownership, institutional ownership, and company growth have no significant effect on debt policy, while free cash flow and company size have a positive effect on debt policy. Then, profitability is able to moderate by weakening the effect of free cash flow and company size on debt policy, and liquidity is able to moderate and strengthen the effect of free cash flow on debt policy. Theoretical Contribution/Originality: This study provides a comprehensive understanding of the complex relationships between managerial ownership, institutional ownership, free cash flow, growth, size, profitability, and liquidity on debt policy. The findings offer valuable insights for policymakers, investors, and corporate managers seeking to optimize their debt policies and financial strategies. Keywords: Debt policy, profitability, liquidity, managerial ownership, institutional ownership, free cash flow, growth, size